Ticagrelor is Not Superior to Clopidogrel in Patients With Acute Coronary Syndromes Undergoing PCI: A Report from Swedish Coronary Angiography and Angioplasty Registry - Sebastian Völz; Petur Petursson; Jacob Odenstedt; Dan Ioanes; Inger Haraldsson; Oskar Angerås; Christian Dworeck; Geir Hirlekar; Anna Myredal; Per Albertsson; Truls Råmunddal; Björn Redfors; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Ticagrelor reduces ischaemic end points in acute coronary syndromes. However, outcomes of ticagrelor versus clopidogrel in real‐world patients with acute coronary syndromes treated with percutaneous coronary intervention (PCI) remain unclear. We sought to examine whether treatment with ticagrelor is superior to clopidogrel in unselected patients with acute coronary syndromes treated with PCI. Methods and Results We used data from SCAAR (Swedish Coronary Angiography and Angioplasty Registry) for PCI performed in Västra Götaland County, Sweden. The database contains information about all PCI performed at 5 hospitals (∼20% of all data in SCAAR). All procedures between January 2005 and January 2015 for unstable angina/non‒ST‐segment‒elevation myocardial infarction and ST‐segment‒elevation myocardial infarction were included. We used instrumental variable 2‐stage least squares regression to adjust for confounders. The primary combined end point was mortality or stent thrombosis at 30 days, secondary end points were mortality at 30 days and 1‐year, stent thrombosis at 30 days, in‐hospital bleeding, in‐hospital neurologic complications and long‐term mortality. A total of 15 097 patients were included in the study of which 2929 (19.4%) were treated with ticagrelor. Treatment with ticagrelor was not associated with a lower risk for the primary end point (adjusted odds ratio [aOR], 1.20; 95% CI, 0.87–1.61; P=0.250). Estimated risk of death at 30 days (aOR, 1.18; 95% CI, 0.88–1.64; P=0.287) and at 1‐year (aOR, 1.28; 95% CI, 0.86–1.64; P=0.556) was not different between the groups. The risk of in‐hospital bleeding was higher with ticagrelor (aOR, 2.88; 95% CI, 1.53–5.44; P=0.001). Conclusions In this observational study, treatment with ticagrelor was not superior to clopidogrel in patients with acute coronary syndromes treated with PCI.